The Rotinonshonni : A Traditional Iroquoian History through the Eyes of Teharonhia:wako and Sawiskera - Rice, Brian, 1955- (Book collections on Project MUSE., 2013)
This book offers a comprehensive history based on the oral traditions of the Rotinonshonni Longhouse People, also known as the Iroquois. Drawing upon J.N.B. Hewitt's translation and the oral presentations of Cayuga Elder Jacob Thomas, the author records the Iroquois creation story, the origin of Iroquois clans, the Great Law of Peace, the European invasion, and the life of Handsome Lake. As a participant in a 700-mile walk following the story of the Peacemaker who confederated the original five warring nations that became the Rotinonshonni, the author traces the historic sites located in what are now known as the Mississippi River Valley, Upstate New York, southern Quebec, and Ontario. The Rotinonshonni creates from oral traditions a history that informs the reader about events that happened in the past and how those events have shaped and are still shaping Rotinonshonni society today. -- Publisher's website.